26 Procedural planning and tip-to-base lampoon to succeed in a complex valve-in-valve TMVR procedure. (8th December 2021) - Baggio, Sara; Lancini, Damiano Regazzoli; Bragato, Renato Maria; Reimers, Bernhard; Pagnotta, Paolo Antonio; Colombo, Antonio
Abstract: Aims: Left ventricle outflow tract (LVOT) obstruction is a feared complication of transcatheter mitral valve replacement (TMVR) procedures. Multimodal imaging evaluation is the key to identify at-risk patient and select the best management. Methods and results: An 83-year-old woman with a history of mitral valve replacement with a 27-mm Carpentier-Edwards bioprosthesis (Edwards Lifesciences, Irvine, CA) for rheumatic heart disease was admitted to our department complaining worsening effort dyspnoea. Clinical evaluation revealed a grade 3/6 holosystolic murmur. She underwent combined transthoracic and transesophageal echocardiography (TEE) which demonstrated mitral bioprosthesis degeneration leading to severe stenosis (mean gradient = 13 mmHg, PHT-derived area = 0.9 cm 2 ) and moderate regurgitation, with preserved biventricular function, and severe pulmonary hypertension (pulmonary artery systolic pression = 65 mmHg). The patient presented a high estimated risk for redo-surgery (Society of Thoracic Surgeons score estimated mortality: 6%) due to her complex medical history, including advanced chronic kidney disease and permanent atrial fibrillation; therefore, she underwent evaluation for valve-in-valve TMVR. Cardiac computed tomography (CT) revealed bioprosthetic anterior leaflet in tight contact with the septum in systole; predicted neo-LVOT using virtual 26-mm Sapien S3 (Edwards Lifesciences, Irvine, CA) valve was 150 mm 2, conferring a high risk of fixed LVOTO. A 26-mm Sapien S3 valve was selected based on CT derived surgical valve ID of 24 mm. After Heart Team discussion, we performed a modified LAMPOON technique to achieve tip-to-base laceration of the bioprosthetic leaflet beside the LVOT, in order to prevent LVOT obstruction. Briefly, after transseptal puncture through right femoral vein access (16 Fr), we crossed the mitral prosthesis using a balloon wedge end-hole catheter, through which we advanced a 300 cm 0.014-inch wire into the ascending aorta, where it was snared from left arterial femoral access (8 Fr) and covered by a micro-catheter. The wire was previously kinked mid-shaft to form a 'flying-V' that was focally denuded and positioned at the target bioprosthetic leaflet's tip using TEE and fluoroscopy. The guidewire was pulled toward the valve ring and electrified at 70 W with continuous 5% dextrose flush until adequate tip-to-base leaflet laceration. Thereafter, we successfully implant a 26-mm Sapien S3 valve. Maximal LVOT gradient post implant was 5 mmHg. The patient was discharged on post-operative day two and she recovered well, reporting functional and symptomatic improvement at 6-month follow-up. Conclusions: our case highlights the importance of multimodality imaging and careful procedural planning to succeed even in complex valve-in-valve TMVR procedures. Transcatheter electrosurgery is an emerging tool for percutaneous structural heart interventions.